Enhancing tofacitinib’s therapeutic efficacy in murine arthritis with a synbiotic formulation comprising Bacillus megaterium DSM 32963 and an Omega-3 fatty acid lysine salt - Zehrer, Annette; Rausch, Alexandra; Jordan, Paul M.; Werz, Oliver; Tom Dieck, Heike; Berngruber, Thomas (Frontiers in Immunology, 2025)
IntroductionOmega-3 polyunsaturated fatty acids (n3-PUFA) are known for their anti-inflammatory benefits, particularly in chronic conditions like rheumatoid arthritis (RA). To resolve an acute inflammation, conversion of n3-PUFA into specialized pro-resolving mediators (SPM) is crucial. Recently, it was shown that the probiotic Bacillus megaterium DSM32963 supports this conversion.MethodsThis study evaluates a synbiotic formulation combining Bacillus megaterium DSM32963 and a unique n3-PUFA-lysine salt as adjunct nutritional supplement to tofacitinib in adjuvant-induced arthritis (AIA) in rats.ResultsOur findings reveal that a combination of low-dose tofacitinib and the synbiotic (ldTofa+Syn) significantly improved all measured arthritis severity parameters, outperforming either single treatment as well as supplementation with a conventional omega-3 ethyl ester that showed no effects on disease severity. The ldTofa+Syn combination also led to a notable reduction in C-reactive protein (CRP) and markers of NETosis in joint tissue, with a significant decrease in neutrophil chemokine CXCL1 observed only in synbiotic-containing groups. Additionally, there was a marked trend towards lower levels of the key inflammatory cytokines TNFα, IL-1β, and IL-6 in the ldTofa+Syn group.ConclusionIn conclusion, the specific synbiotic formulation shows promise as a complementary nutritional therapy for RA, improving disease outcomes and modulating immune responses.